Social media competence and digital citizenship among college students. (August 2019) - Xu, Shun; Yang, Harrison Hao; MacLeod, Jason; Zhu, Sha
The global emergence of new media and social change have drawn attention to the topic of digital citizenship. Previous literature has examined individuals' digital citizenship with some determinants of technology use. However, individuals' level of social media competence (SMC) has not yet been examined in relation to digital citizenship. To increase knowledge of the ingredients that may be important for education programs to improve individuals' digital citizenship, this study examined SMC and digital citizenship among 772 college students. The results identified that five of the six social media competencies examined were predictors of individuals' digital citizenship. These findings provided empirical evidence of a relationship between SMC and digital citizenship, which should be considered by researchers and practitioners when formalizing educational programs, developing curricula, and designing pedagogy for improving individuals' digital citizenship.